1999
DOI: 10.1055/s-2007-978686
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone Exhibits Immunomodulatory Activity on the Cytokine Production of Activated Human Lymphocytes

Abstract: Troglitazone (TGL), a thiazolidinedione compound that improves the response of peripheral target tissue to insulin, also has anti-inflammatory properties, a potential means of protection from Type 1 (insulin dependent) diabetes. In order to test the ability of TGL to affect cytokine production, peripheral blood mononuclear cells from healthy donors were exposed to TGL in the presence or absence of a polyclonal activator (PHA) and the production of cytokines assayed. TGL enhanced PHA response, promoted secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Troglitazone has been shown to inhibit the hepatitis-B virus 66 and has immunomodulatory effects on cytokine production. 157 It has also been shown to significantly reduce IL-6 levels. 158 …”
Section: Discussionmentioning
confidence: 99%
“…Troglitazone has been shown to inhibit the hepatitis-B virus 66 and has immunomodulatory effects on cytokine production. 157 It has also been shown to significantly reduce IL-6 levels. 158 …”
Section: Discussionmentioning
confidence: 99%
“…Giorgini et al reported that troglitazone reduced proinflammatory cytokines, such as TNF-a and IFN-g in vitro. 4 Augstein et al showed that troglitazone reduced IFN-g expression in splenic T cells in NOD mice. 2 Therefore, it has been hypothesized that thiazolidinediones prevent autoimmune diabetes by suppressing the Th1 skewing of the Th1/Th2 balance seen at the onset of diabetes in NOD mice.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that TZDs increase insulin synthesis and the insulin content of islet cells in addition to improving the secretory response of islets [19]. In addition to its hypoglycaemic effect, TGL has been shown to possess in vitro antiinflammatory properties as shown by the reduction of cytokines such as TNF-a and IFN-c [20]. TZD activators have been shown to exert anti-inflammatory activities in various cell types by inhibiting the expression of proinflammatory genes such as cytokines, metalloproteases and acute-phase proteins [21].…”
Section: Discussionmentioning
confidence: 99%